A Lithium–Sulfur Battery using a 2D Current Collector Architecture with a Large‐Sized Sulfur Host Operated under High Areal Loading and Low E/S Ratio. Issue 46 (4th October 2018) - Li, Matthew; Zhang, Yining; Bai, Zhengyu; Liu, Wen Wen; Liu, Tongchao; Gim, Jihyeon; Jiang, Gaopeng; Yuan, Yifei; Luo, Dan; Feng, Kun; Yassar, Reza S.; Wang, Xiaolei; et al.
Abstract: While backless freestanding 3D electrode architectures for batteries with high loading sulfur have flourished in the recent years, the more traditional and industrially turnkey 2D architecture has not received the same amount of attention. This work reports a spray‐dried sulfur composite with large intrinsic internal pores, ensuring adequate local electrolyte availability. This material offers good performance with a electrolyte content of 7 µL mg −1 at high areal loadings (5–8 mg cm −2 ), while also offering the first reported 2.8 µL mg −1 (8 mg cm −2 ) to enter into the second plateau of discharge and continue to operate for 20 cycles. Moreover, evidence is provided that the high‐frequency semicircle (i.e., interfacial resistance) is mainly responsible for the often observed bypassing of the second plateau in lean electrolyte discharges. Abstract : Cyclability of a low‐electrolyte‐content, high‐areal‐sulfur electrode is achieved through the development of an agglomerated structure composed of large‐scale hollow materials. Detailed in situ impedance and X‐ray diffraction analysis reveal interesting characteristics of sulfur cells operating under lean electrolyte conditions.